SPATIAL DESIGN CONSIDERATIONS FOR UPLIFTING STUDENT’S SOCIETAL PERSONA- A CASE OF UNIVERSITY OF PESHAWAR - Waqas, Muhammad; Shah, Syed Akhtar Ali; Yaseen, Aneela; Jawad, Muhammad; Sarir, Saima (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: This study pursues to find the gap between prudently programmed pure academics in the university and student’s societal persona, a result of impulsive learning and informal socializing. This is piloted to justify the need for properly designed informal socializing spaces by comparing actual and proposed spaces at the university campus. Methodology: A mixed-method strategy is adopted to conduct this research; the theoretical basis is formulated by available literature, and a detailed precedent study is carried out to establish programmatic assumptions in the light of contemporary handling of a similar subject. Visual survey and spatial analysis of building spaces in relationship with human behaviour are performed to analyse preferences of multiple users. Main Findings: The research culminates in a set of propositions put forth to initiate a purpose-built space that can informally regulate and enhance the social experience in existing academia through spatial design by overall massing of solids and voids, while considering ventilation and thermal comfort through Interconnected Courtyard System, Wind conduits, etc. Applications of this study: The guidelines are formulated for functional, environmental, and Socio-Psychological aspects to design informal socializing spaces. Novelty/Originality of this study: Despite learning only from text and oral faculty teachings, the overall milieu of the University through such spaces will add in student’s positive personality growth altogether that is ignored in most of the cases.